Comparison of Apical debris Extrusion of ProTaper Universal rotary and SafeSiders reciprocal Systems : debris Extrusion of ProTaper Universal and SafeSiders - Ahangari, Zohreh; Naseri, Mandana; Soleimani, Arash; Yazdani, Atoosa; Mehrabani, Mahgol (Journal of Dental School, 2024)
Objectives During root canal preparation, dentinal chips, irrigants, and pulp remnants are extruded into the pre-radicular space. This phenomenon may lead to post-endodontic flare-ups. Furthermore, different preparation systems may be associated with varying amounts of apically extruded debris. This study aimed to compare the amount of debris extrusion using two endodontic preparation systems: ProTaper Universal and SafeSiders. Methods In this in vitro study, 30 single-rooted human mandibular premolars with fully developed apices and curvatures of 0-10 degrees were randomly assigned to two groups (N=15). The root canals were prepared with the ProTaper Universal and the SafeSiders system according to the manufacturer’s instructions. Extruded debris was collected into pre-weighed tubes by washing the apical foramen area with 1cc of distilled water. After incubating tubes for ten days to evaporate the remaining irrigants, the amount of apically extruded debris was calculated by subtracting each tube’s initial and final weight. Data were analyzed by Student t-test at P<0.05. Results The mean values for the amount of apically extruded debris using ProTaper Universal and SafeSiders system were 0.0018±0.0004 g and 0.0023±0.0006 g, respectively. The two groups had a statistically significant difference regarding the amount of the apically extruded debris. The SafeSiders system caused significantly more debris extrusion than the ProTaper Universal system (p<0.01). Conclusion Both the ProTaper Universal rotary system and the SafeSiders reciprocating system caused apical debris extrusion; However, ProTaper Universal was associated with less debris extrusion.